The prevalence of e-cigarette use among adults in Malaysia - Ab Rahman, Jamalludin; Mohd Yusoff, Muhammad Fadhli; Nik Mohamed, Mohamad Haniki; Mahadir Naidu, Balkish; Lim, Kuang Hock; Tee, Guat Hiong; Mohamad, Maria Safura; Kartiwi, Mira; Draman, Samsul; Ab Rahman, Norny Syafinaz; Aris, Tahir (SAGE Publishing, 2019)
Electronic cigarettes (e-cigarettes) are a new method for the consumption of nicotine. A nationwide survey among 4288 Malaysian adults was conducted in 2016 to measure the prevalence and to describe the population characteristics of e-cigarette users. A complex sampling design was used, and data were collected using a face-to-face questionnaire. The overall prevalence of current, ever, former, and dual users of e-cigarettes in Malaysia were 3.2% (95% confidence interval [CI] = 2.5-4.1), 11.9% (95% CI = 10.5-13.5), 8.6% (95% CI = 7.5-9.8), and 2.3% (95% CI = 1.8-3.1), respectively. The prevalence of all type of e-cigarette use was higher in urban than in rural areas. Current e-cigarette users were likely to be younger, males, and with higher education level. Among current e-cigarette users, 74% (95% CI = 64-82) also smoked conventional cigarettes (dual user). E-cigarette use is prevalent in Malaysia. It is common among younger adults, males, and cigarette smokers.